Associations between PTSD and intimate partner and non-partner aggression among substance using veterans in specialty mental health. (January 2017) - Buchholz, Katherine R.; Bohnert, Kipling M.; Sripada, Rebecca K.; Rauch, Sheila A.M.; Epstein-Ngo, Quyen M.; Chermack, Stephen T.
Abstract: Background: Risk factors of violence perpetration in veterans include substance use and posttraumatic stress disorder (PTSD); however, it is unknown whether these factors are associated with greater risk for partner or non-partner violence. This study investigated the associations between probable PTSD, heavy drinking, marijuana use, cocaine use, and partner and non-partner violence perpetration. Methods: Self-report questionnaires assessing past-year partner and non-partner aggression (CTS2) as well as past-month substance use (SAOM), probable PTSD (PCL-C), and probable depression (PHQ-9) were administered to 810 substance using veterans entering VA mental health treatment. Results: In bivariate analyses, probable PTSD in substance using veterans was associated with violence perpetration (partner physical, χ 2 = 11.46, p = 0.001, φ = 0.12; non-partner physical, χ 2 = 50.64, p < 0.001, φ = 0.25; partner injury, χ 2 = 6.41, p = 0.011, φ = 0.09; non-partner injury, χ 2 = 42.71, p < 0.001, φ = 0.23). In multiple logistic regression analyses that adjusted for sociodemographic characteristics, probable PTSD was independently associated with non-partner physical (odds ratio [ OR ], 2.82; 95% confidence interval [CI], 1.97–4.05) and injury aggression ( OR, 3.96; CI, 2.56–6.13). Cocaine and heavy drinking were independently associated with non-partner physical and injury aggression and non-partner injury aggression respectively. Conclusions: The results provide evidence that probable PTSD, heavy drinking, and cocaine use are associated with increased risk of non-partner violence perpetration in substance using veterans. These results underscore the importance of screening for PTSD symptoms and violence perpetration towards non-partners in substance using veterans presenting for treatment. Highlights: The study examined PTSD and partner/non-partner aggression in substance using veterans. Probable PTSD was associated with non-partner aggression at different severity levels. Probable depression was significantly associated with more severe partner aggression. Future research is needed to determine what treatments may be effective in decreasing aggression.